Advances in Nanoparticles as Anticancer Drug Delivery Vector: Need of this Century - Ali, Imran; Mukhtar, Sofi D.; Ali, Heyam S.; Scotti, Marcus T.; Scotti, Luciana (Current Pharmaceutical Design, 2020)
Background: Nanotechnology has contributed a great deal to the field of medical science. Smart drugdelivery vectors, combined with stimuli-based characteristics, are becoming increasingly important. The use of external and internal stimulating factors can have enormous benefits and increase the targeting efficiency of nanotechnology platforms. The pH values of tumor vascular tissues are acidic in nature, allowing the improved targeting of anticancer drug payloads using drug-delivery vectors. Nanopolymers are smart drug-delivery vectors that have recently been developed and recommended for use by scientists because of their potential targeting capabilities, non-toxicity and biocompatibility, and make them ideal nanocarriers for personalized drug delivery. Method: The present review article provides an overview of current advances in the use of nanoparticles (NPs) as anticancer drug-delivery vectors. Results: This article reviews the molecular basis for the use of NPs in medicine, including personalized medicine, personalized therapy, emerging vistas in anticancer therapy, nanopolymer targeting, passive and active targeting transports, pH-responsive drug carriers, biological barriers, computer-aided drug design, future challenges and perspectives, biodegradability and safety. Conclusion: This article will benefit academia, researchers, clinicians, and government authorities by providing a basis for further research advancements.
Keywords: nanoparticles